Integration between sales and marketing CRM for data-driven decision making: an analysis from the perspective of specialists and users - Santana, Bruna Gabrielle Rodrigues; Luche, José Roberto Dale; Freitas, Claudia Regina de (Brazilian Journal of Production Engineering, 2026)
Over time, CRM has evolved significantly from its origins as a simple contact repository to becoming a data platform used in business intelligence. This study explores, from the perspective of experts and users, how the integration between Sales and Marketing CRM systems can benefit data-driven decision making. A qualitative methodological approach was used, with a literature review and semi-structured interviews with professionals from different areas of expertise. Data analysis was performed using the Iramuteq software, employing the similarity analysis method. The results show that the interconnection between CRMs provides a consolidated view of the customer, enables more accurate identification of opportunities, and improves the efficiency of marketing campaigns and sales actions. Based on these findings, twelve practical indicators are proposed to help companies measure the benefits of integration. The conclusion reached is that this research can strengthen the domain of information systems, which reaffirms the relevance of the association between the areas of marketing and sales as a strategic factor in data-driven contexts.
Keywords: CRM; system integration; decision-making; sales; digital marketing